ENGLISH: - - Silaen, Elperinda; Afriana, Afriana (BASIS (Bahasa dan Sastra Inggris), 2024)
Abstract This study has target to find lexical cohesion in the text of a speech delivered by a controversial president, Donald Trump. The researcher also reveals several reasons why the writing problem is on lexical cohesion where cohesive devices play an important role in shaping a speech and the use of language that is organized and easily understood by others in delivering a speech will have an impact on communication that goes well, so as to avoid misunderstandings between speakers and listeners. Therefore, the method used in this research is qualitative and this descriptive qualitative research also used observational method and note taking technique. In supporting data collection techniques, researchers use the theory of Creswell (2018) and also support by Merriam &Tisdell (2016) .The next by Litosseliti (2010). The lexical cohesion proposed by Matthienssen & Halliday, (2014) has several types of lexical cohesion consist of repetition, synonymy, antonymy, hyponymy, and meronymy. For the results of data analysis, there are 50 repetitions then 1 hyponymy then 1 meronym, 2 synonyms, and finally 1 antonym. Keywords: Speech Script, Cohesion, Lexical cohesion, Qualitative